The elephant in the room : sharing the secrets for pursuing real financial success - Bridger, Barry (Wiley, 2009)
The Elephant In The Room. A financial fable filled with lessons for building long-term wealth. "What most people don't understand, and what usually turns out to be the elephant in the room, is their behavior. It affects everything in your life, including the way you earn, spend, and save."--Aunt Katherine. Michael Davidson and his wife, Jennifer, knew what they wanted from life and had some pretty good financial habits, but they were far from prepared for the future. Despite a healthy income and successful career, Michael--who's facing down thirty, with a wife who also works, and two